Intelligent Robotics and Applications Third International Conference, ICIRA 2010, Shanghai, China, November 10-12, 2010. Proceedings, Part I - Liu, Honghai; Ding, Han.; Xiong, Zhenhua; Zhu, Xiangyang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the Third International Conference on Intelligent Robotics and Applications, ICIRA 2010, held in Shanghai, China, in November 2010. The 140 revised full papers presented were thoroughly reviewed and selected from numerous submissions. They are organized in topical sections on bionic dexterous hand; modeling and control systems involving hysteresis; control system modeling and applications; intelligent control and their applications; robot and automation in tunneling; robot mechanism and design; service robotics; computer vision and applications; sensor design, multi-sensor data fusion; industrial process control, manufacturing processes, and automation; mobile robotics; theory applications of heavy manipulators; robot vision; biomedical and rehabilitation engineering, and medical robotics; human-friendly robot partners; surface inspection, modeling and machining; modeling for robotics and manufacturing automation; robot and investigation.
Bionic Dextrous Hand -- Modeling and Control of Systems Involving Hysteresis -- Control System Modeling and Applications -- Intelligent Control and Their Applications -- Robot and Automation in Tunneling -- Robot Mechanism and Design -- Service Robotics -- Computer Vision and Applications -- Sensor Design, Multi-sensor Data Fusion.
Keywords: Computer science; Computer Communication Networks; Information systems; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Information Systems Applications (incl.Internet).; Computer Communication Networks